Stromal derived factor-1 (SDF-1) and its receptors CXCR4 and CXCR7 in endometrial cancer patients. - Malgorzata Walentowicz-Sadlecka (Public Library of Science (PLoS), 2014)
Purpose One of the most important function of stromal derived factor-1 (SDF-1) and its receptors, is regulating the process of metastasis formation. The aim of our study was to investigate the correlation between SDF-1, CXCR4 and CXCR7 protein levels measured by immunohistochemistry with the clinicopathological features and the survival of endometrial cancer patients. Materials and methods 92 patients aged 37-84 (mean 65.1±9.5) were enrolled to our study between January 2000 and December 2007. After the diagnosis of endometrial cancer, all women underwent total abdominal hysterectomy, with bilateral salpingoophorectomy and pelvic lymph node dissection. In all patients clinical stage (according to FIGO classification), histologic grade, myometrial invasion, lymph node and distant metastases were determined.Furthermore, the survival time was assessed. Immunohistochemical analyses of SDF-1, CXCR4 and CXCR7 were performed on archive formalin fixed paraffin embedded tissue sections. Results Statistically significant correlations (p<0.01) were reported between SDF-1 and the clinical stage of disease, lymph node metastases, distant metastases, deep myometrial invasion (≥50%), cervical involvement, involvement of adnexa. Statistically significant correlation (p<0.01) was found between SDF-1 expression and the risk of the recurrence. Higher SDF-1 expression was associated with a higher risk of recurrence (p = 0.0001). The results of CXCR4 and CXCR7 expression didn't reveal any significant differences(p>0.05) between the proteins expression in the primary tumor cells and the clinicopathological features. Moreover, the Kaplan-Meier analyses demonstrated a stepwise impairment of cancer overall survival (OS) with increasing SDF-1 expression. Conclusion The important role of SDF-1 as a predictor of negative clinicopathological characteristics of a tumor suggests that the expression of this stromal factor should be included in the panel of accessory pathomorphological tests and could be helpful in establishing a more accurate prognosis in endometrial cancer patients.